Eliminating Guilt by Association: Reviewing the Limits of Ezokola in Canadian Refugee Law Complicity Decision‑Making (2013–2020) - Bajic, Aneta; He, Chun; Koltun, Andrew (Ottawa Law Review / Revue de droit d’Ottawa)

(untitled) (Ottawa Law Review / Revue de droit d’Ottawa, 2023)
A recurring question in Canadian and international refugee law has been when to exclude individuals from refugee protection based on their connection to international crimes. Article 1F(a) of the 1951 Refugee Convention excludes from protection those who have committed a crime against peace, a war crime, or a crime against humanity as defined under international law. The central concept is that of “complicity”: what level of involvement or connection with such crimes makes a person morally culpable, such that they should be excluded from refugee protection?In 2013, the Supreme Court of Canada in Ezokola created a new test for complicity to break free from past patterns of excluding claimants based on guilt by association. The Court determined that exclusion from refugee protection is warranted only where the individual made a voluntary, knowing, and significant contribution to the crimes or criminal purposes of the group in question.This paper evaluates the degree to which Canadian refugee law has made a definitive break with findings that amount to guilt by association for the purposes of Article 1F(a) of the 1951 Refugee Convention in the ten years since the Ezokola decision.Our analysis suggests that, while the Ezokola decision had a positive impact, aspects of Ezokola’s analytical framework are unclear and inconsistently applied. Ultimately, further guidance is required if we are to fully realize Ezokola’s objective of eliminating exclusion findings that amount to guilt by association.